Application of the interventional limb raising management strategy (ILRMS) at radial vascular access sites in coronary angiography and percutaneous coronary intervention: A randomized trial - Wen-Jie Zhang; Jin-Chuan Yan; Zhong-Qun Wang (Elsevier, 2016)
Purpose: To compare the effectiveness of the interventional limb raising management strategy (ILRMS) to elastic bandage compression at radial vascular access sites following coronary angiographies (CAGs) and percutaneous coronary interventions (PCIs). Methods: Patients with ischemic coronary heart disease whose condition was stable over three months were enrolled in this clinical study (n = 590; aged 25-80). All participants had just undergone CAG and PCI. Patients were randomized into either the ILRMS group (n = 360) or standard post-intervention care with an elastic bandage (n = 230). Overall comfort and wrist pain was assessed and the degree of index finger swelling and oxygen saturation was measured on the affected arm. All variables were measured prior to post-intervention treatment and again at six hours after CAG and PCI. Results: We found that patients receiving ILRMS had significantly lower wrist pain scores and swelling around the index finger compared to the elastic bandage group (p < 0.05). Oxygen saturation of the index finger was not statistically significant (p > 0.05). We also found that 19.57% of the elastic bandage patients were comfortable, while ILRMS patients were significantly more comfortable (93.06%; p < 0.05). Conclusions: We find that ILRMS alleviates swelling and pain of the wrist more effectively than current practices and improves the degree of overall comfort of patients who undergo CAG and PCI. Keywords: Interventional limb raising management strategy, Coronary angiography, Percutaneous coronary intervention, Nursing